The Determinants of Corporate Sustainability Reporting Disclosures: Evidence from the Listed Manufacturing and Finance Companies in the Colombo Stock Exchange - Karunathilaka, K.A.C.S.; Karunaratne, W.V.A.D.K. (Department of Accountancy, Faculty of Commerce and Management Studies, University of Kelaniya, 2020)
The term “corporate sustainability” describes a new corporate management model. These include the linkages between environmental, social, and economic issues as well as long-term perspectives. The goal is to provide long-term value for stakeholders without compromising people, the planet, or the economy. This study investigates the impact of determinants on corporate sustainability reporting (CSR) disclosure. While many studies have investigated sustainability reporting in developed countries, there is a dearth of research in developing countries. As a developing country in the Sri Lankan context, it was confirmed that a few times and the researchers gave comparatively less attention to investigate the impact of firms’ specific determinants on sustainability reporting disclosures in Sri Lanka. Thus the study aimed to investigate the impact of firm characteristics on corporate sustainability reporting in Sri Lanka related to the Manufacturing sector and Finance sector. In the study, the firm’s age, firm size, Leverage, Firm profitability, Ownership concentration, Management qualification are considered as independent variables. Those variables are measured by using the total asset, the number of listed years, Total debt to total asset ratio, Return on equity, Common shares owned by individual investors, Degree holding, respectively. The dependent variable of CSR was measured by using the Global Reporting Initiatives (GRI) index. Consequently, these quantitative data were employed in the panel data regression model using EViews software to scientifically analyze the data to identify the significant relationship between these two variables. This study helps the shareholders and investment community evaluate the firm and get the optimum decisions. Furthermore, the management can also get knowledge for making decisions and making differences by getting efficient outcomes from that.
Keywords: CSR, GRI, Manufacturing Sector, Finance Sector, Sri Lanka